2008
DOI: 10.1002/hep.22532
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-dependent protein kinase C isoforms are critical to estradiol 17β-D-glucuronide-induced cholestasis in the rat

Abstract: The endogenous estradiol metabolite estradiol 17␤-D-glucuronide (E 2 17G) induces an acute cholestasis in rat liver coincident with retrieval of the canalicular transporters bile salt export pump (Bsep, Abcc11) and multidrug resistance-associated protein 2 (Mrp2, Abcc2) and their associated loss of function. We assessed the participation of Ca 2؉ -dependent protein kinase C isoforms (cPKC) in the cholestatic manifestations of E 2 17G in perfused rat liver (PRL) and in isolated rat hepatocyte couplets (IRHCs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
85
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 39 publications
5
85
0
Order By: Relevance
“…Furthermore, an increase in membrane translocation of PKC« was observed, which suggests activation, although there was no change in phosphorylation. Although these data suggest that MARCKS may not be involved in NASH-related Mrp2 mislocalization, PKC« phosphorylates Mrp2 directly to alter the transport function, and the translocation of PKC« to the membrane may be related to this alternative function (Crocenzi et al, 2008). Furthermore, there may be other substrates for PKC« at the canalicular membrane that mediates Mrp2 retrieval in response to other stimuli.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Furthermore, an increase in membrane translocation of PKC« was observed, which suggests activation, although there was no change in phosphorylation. Although these data suggest that MARCKS may not be involved in NASH-related Mrp2 mislocalization, PKC« phosphorylates Mrp2 directly to alter the transport function, and the translocation of PKC« to the membrane may be related to this alternative function (Crocenzi et al, 2008). Furthermore, there may be other substrates for PKC« at the canalicular membrane that mediates Mrp2 retrieval in response to other stimuli.…”
Section: Discussionmentioning
confidence: 81%
“…Many of these pathways overlap in the use of these mediators, creating a complex regulation of localization, even when looking at just one transporter. For example, activation of PKCa, a calciumdependent protein kinase, has been shown to be involved in both TUDCAstimulated Mrp2 insertion and estradiol-17b-D-glucuronide-induced Mrp2 Altered Membrane Localization in NASH retrieval (Crocenzi et al, 2008;Wimmer et al, 2008). Mrp2 membrane insertion by PKCa is dependent upon the cooperation of PKA; moreover, Mrp2 insertion is also mediated, in a cAMP-dependent manner, by PKCd (Crocenzi et al, 2008;Park et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea that PKC activation influences transport processes is highlighted by a recent publication of Crocenzi et al (60), which investigated the influence of protein kinase C isoforms on estradiol 17␤-D-glucuronide (E 2 G)-induced acute cholestasis. They demonstrated that E 2 G activates PKC␣ in primary cultured rat hepatocytes and induces retrieval of Mrp2 and Bsep from the apical membrane, which normally provide the driving force for osmotic bile formation.…”
Section: Discussionmentioning
confidence: 99%
“…Tauroursodeoxycholic acid acts via the same pathway but also via the activation of various protein kinase C isoforms. Protein kinase Ca recruitment by estradiol-17b-D-glucuronoside decreases canalicular ABCB11 expression in rodents, which could partly be responsible for its cholestatic properties (Crocenzi et al, 2008). Inflammation-induced cholestasis finally can lead to a decreased ABCB11 insertion into the canalicular membrane in vitro and in rodents.…”
Section: Abcb11mentioning
confidence: 99%